Nonlinear coupled Liouville-Caputo fractional differential equations with a new class of nonlocal boundary conditions - Ahmad, Bashir; Alsaedi, Ahmed; Alotaibi, Fawziah M.; Alghanmi, Madeaha (Mathematical notes (Miskolci Egyetem (Hungary)), 2023)
In this paper, we study a coupled system of nonlinear Liouville-Caputo fractional differential equations equipped with a new set of nonlocal boundary conditions involving an arbitrary strip together with two sets of nonlocal multi-points on either part of the strip on the given domain. We emphasize that the boundary conditions considered in this study are formulated with respect to the sum and difference of the unknown functions. We apply the well-known tools of the fixed point theory to derive the main results. Examples are presented for the illustration of the obtained results.